Dietary glutamine improves meat quality, skeletal muscle antioxidant capacity and glutamine metabolism in broilers under acute heat stress. Issue 1 (1st January 2018) - Sifa, Dai; Bai, Xi; Zhang, Dan; Hu, Hong; Wu, Xuezhuang; Wen, Aiyou; He, Shaojun; Zhao, Lei
ABSTRACT: This study investigated the effects of glutamine (Gln) on meat quality, skeletal muscle antioxidant capacity and Gln metabolism in heat-stressed broilers. Three hundred 42-day-old broilers were randomly divided into five groups: a control group (23 ± 1°C), which was fed basal diet, and four experimental groups (34 ± 1°C), supplemented with 0, 5, 10, and 20 g Gln/kg of basal diet. The experiment lasted for 24 h. Compared with the control group, acute heat stress caused a significant reduction ( p < .05) in meat pH, water-holding capacity (WHC), gumminess and hardness, and a significant increase ( p < .05) in cooking loss (CL) and lightness ( L *) values. However, dietary Gln (20 g/kg) increased ( p < .05) meat pH, WHC, gumminess and hardness, but decreased ( p < .05) meat CL and L * values in the acute heat-stressed group. In breast and thigh muscles, the acute heat stress group exhibited significantly ( p < .05) higher concentrations of malondialdehyde (MDA), but significantly ( p < .05) lower levels of Gln, glutamate and glutaminase than the control group; dietary 20 g/kg Gln significantly decreased ( p < .05) MDA concentrations, while it increased ( p < .05) glutathione, glutathione peroxidas, T-AOC, Gln, glutamate, and glutaminase levels in acute heat-stressed groups. Gln could increase meat quality by improving antioxidative capacity and Gln metabolism in heat-stressed broilers.